2023
DOI: 10.11646/zootaxa.5297.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Pseudolaguvia permaris, a new catfish from the Eastern Ghats of India (Teleostei: Sisoridae)

Abstract: Pseudolaguvia permaris, a new sisorid catfish is described from the Mahanadi River basin in Odisha, India. The new species can be distinguished from congeners in having the following combination of characters: serrated anterior margin of dorsal-fin spine, thoracic adhesive apparatus not extending beyond base of last pectoral-fin ray, caudal peduncle depth 8.6–10.2% SL, body depth at anus 15.3–20.2% SL, adipose-fin base length 13.6–18.1% SL, dorsal to adipose distance 11.4–14.4% SL, length of pectoral-fin spine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The discovery of A. crassioris demonstrates that the distribution pattern of the genus Amblyceps in India is presently conformable with another sisoroid catfish genus, Pseudolaguvia Misra, 1976 (see Vijayakrishnan et al, 2023). Increasing evidence has shown that widespread species, which are often recognized as a single species due to very similar or indistinguishable morphology, can comprise multiple species (Bickford et al, 2007).…”
Section: Author Contributionsmentioning
confidence: 97%
“…The discovery of A. crassioris demonstrates that the distribution pattern of the genus Amblyceps in India is presently conformable with another sisoroid catfish genus, Pseudolaguvia Misra, 1976 (see Vijayakrishnan et al, 2023). Increasing evidence has shown that widespread species, which are often recognized as a single species due to very similar or indistinguishable morphology, can comprise multiple species (Bickford et al, 2007).…”
Section: Author Contributionsmentioning
confidence: 97%